How Influenced Management Behavior is on the Implementation of Total Quality Management (TQM) and Company Operational Performance - Wiyatno, Tri Ngudi; Kurnia, Hibarkah; Zulkarnaen, Iskandar; Nuryono, Arif (International Journal of Industrial Engineering and Management, 2024)
The implementation of TQM to improve product quality does not only focus on systems and technology but also requires competent human resources such as leadership, technical competence, and organizational culture as users and controllers of systems and technology. This will have an impact on the company's operational performance which is expected to continue to increase. This research aims to analyze and test the influence of leadership, technical competence, and organizational culture on the implementation of Total Quality Management (TQM) and its impact on operational performance. The research method used is a descriptive statistical method with an explanatory type. The sampling technique was carried out in a proportional cluster, randomly sampling all ceramic workers in 4 different companies with a total of 368 respondents. The analysis technique used is Covariance based Structural Equation Modeling (SEM) analysis, and the application used is Lisrel. The research results show that leadership directly influences the implementation of TQM to run well as 33,80%. Technical competition directly influences TQM at 21,10%. Organizational culture has a direct influence on TQM at 16,70%. Article history: Received (December 30, 2023); Revised (May 30, 2024); Accepted (June 24, 2024); Published online (August 9, 2024)